A test station to verify the calibration of optical dioptometer - Distasio, Anthony J. (Engineering cases, 2013)
Engineers who work in the optical manufacturing industry often encounter the need to verify the correct calibration of instruments they use. It is common to use the services of companies specializing in calibration, or alternatively, to send an instrument to its manufacturer for a certification. This engineering case describes a situation where none of the local calibration firms could calibrate a specific dioptometer, which was being used in critical steps of their manufacturing process for several optical products. The in-house engineers had to devise their own calibration techniques that were repeatable, accurate, and could be vetted by the manufacturer before implementation.